PEMANFAATAN MEDIA DIGITAL DINAS KESEHATAN TERHADAP PENANGANAN HUMAN IMMUNODEFICIENCY VIRUS DI BANDA ACEH - Hanifah Nurdin; Muhammad Aminullah; Muhammad Fathin Hafizd (Fakultas Agama Islam Universitas Muhammadiyah Bengkulu, 2026)
Digital media plays a strategic role in public health communication, including in the dissemination of information about Human Immunodeficiency Virus (HIV). However, the effectiveness of digital communication is not only determined by the availability of platforms, but also by strategic planning, internal collaboration, and message sustainability. This study aims to analyse the use of digital media by the Banda Aceh City Health Office in communicating HIV to the public. This study uses a qualitative approach with in-depth interviews, observation, and documentation methods. The research informants consisted of those responsible for HIV programmes and digital media managers within the Health Office. Data analysis was carried out through the stages of data reduction, data presentation, and thematic conclusion drawing. The results of the study indicate that the use of digital media in HIV communication is still not optimal. This can be seen from the limited consistency and continuity of content on various digital platforms, so that HIV issues have not been established as a strong health communication agenda in the public sphere. In addition, differences in educational backgrounds between those responsible for HIV programmes and digital media managers have become structural barriers to health communication. The separation of roles between health content developers and technical communication implementers has resulted in HIV messages tending to be delivered in an informative and normative manner, without a collaborative and persuasive communication strategy. This study also found that HIV messages are simplified in an effort to avoid stigma and discrimination against survivors. Although ethically relevant, simplifying messages has the potential to limit the depth of public understanding of HIV issues. Furthermore, the absence of a sustainable digital communication strategy has resulted in reactive and momentum-based HIV communication, preventing digital media from functioning optimally as a means of improving public health literacy. The Banda Aceh City Health Office's use of digital media in HIV management has not been managed strategically and sustainably. Long-term communication planning, cross-sector collaboration, and a communication approach that can improve health literacy while minimising stigma in the community are needed.